Primary Endometroid Carcinoma of Fallopian Tube – A Case Report - Sohail, Summaya; Khalid, Ahmareen; Khattak, Asma (International Journal of Pathology, 2018)
Background: Reported cases of primary carcinoma of fallopian tube can be numbered. Owing to the emergingimportance of this “small organ” in the previous few years as a precursor lesion of many gynecologicalmalignancies, the need of the hour is to understand all the pathophysiological aspect of this uncommon neoplasmCase Presentation: Keeping in mind the above-mentioned rationale we hereby take the opportunity to present acase Primary Endometroid Carcinoma of fallopian tube in a 60 years old patient Stage pT2a, who presented withthe complains of Abdominal swelling and pain. As with nearly all the cases reported of fallopian tube carcinomasits always the pathologist who first diagnose the case of primary carcinoma of fallopian tube.The patientsradiological findings were consistent with adnexal mass with inseparable plane between ovary and fallopiantube. Extensive sampling of both the fallopian tube, ovary and were done keeping in view the set criterion fordiagnosis of primary fallopian tube cancer